Removal of tritium from vacuum vessel by RF heated plasmas in LHD. (17th August 2021) - Tanaka, M; Kato, H; Suzuki, N; Chimura, H; Masuzaki, S; Takahashi, H; Seki, T; Osakabe, M
Abstract: The tritium removal from the vacuum vessel is one of the key issues for the realization of a fusion reactor. As in situ tritium removal techniques from the plasma facing materials, helium glow discharge wall conditioning (GDWC) and RF heated plasma due to electron cyclotron wall conditioning (ECWC) and ion cyclotron wall conditioning (ICWC) are applied with Large Helical Device (LHD) which remains tritium produced by deuterium plasma experiment. As the result, it suggests that ICWC could remove the tritium more efficiently than the ECWC and the GDWC. In the ICWC operation, the high energy particles induced by the minority ion heating mode as the standard ICRF heating operation may play an important role in tritium removal from the plasma-facing materials due to the particle's bombardment.